Anti-tumor agent celecoxib activity towards SP-C1 tongue cancer cells invasion (in vitro) - Harun Achmad; Mieke Hemiawati Satari; Roosje Rosita Oewen; S. Supriatno (Faculty of Dentistry Universitas Padjadjaran, 2011)
Invasion is a characteristic of the occurrence of cancer and indicates the cancer cells' capability to destroy and degrade the border between the epithet and basal membrane to further spread into the surrounding extra-cellular matrix. The purpose of this research was to find the existence of impediment at the SP-C1 tongue cancer cell using celecoxib chemopreventive medication. The SP-C1 tongue cancer cells were treated in vitro using celecoxib medication as a research subject at the following concentrations 5, 10, 25, 50, 75, 100, 125%; and 0 as control group (only DMEM growth medium treatment). Pure experimental testing was carried out for 24 and 48 hours, with observation and calculation of an average number of SP-C1 tongue cancer cells. The data collected were analyzed using the ANOVA test with Newman Keuls paired range test or t-test. Research results indicated that the average number of SP-C1 tongue cancer cells invasion after administration of celecoxib medication based on administration concentration and time statistically yielded significant results. The ANOVA test results were statistically significant, that is, average occurrence of the number of SP-C1 tongue cancer cells due to the use of celecoxib at certain concentrations compared to that without celecoxib was different. At celecoxib of zero (control) concentration was 24.4 with celecoxib concentration starting at 5 up to 125% experienced a decline from its average 11 to become 2.3. The conclusion of the research was that the greater the celecoxib concentration administered, the greater the effect on the impediment of SP-C1 tongue cancer cell invasion.